MEASUREMENT OF NEUTRON SPATIAL DISTRIBUTION OF THE BNCT EPITHERMAL BEAM AT THE REACTOR LVR-15 - Michaela Rabochová; Miroslav Vinš; Jaroslav Šoltés; Božena Michalcová (Acta Polytechnica CTU Proceedings)
In this study, a measurements of neutron field using a special positioning device with a 6Li + Si detector and image plate is described. The measurements were provided for Boron Neutron Capture Therapy (BNCT) channel of the LVR-15 reactor in the Research Centre Rez Ltd., Czech Republic. Mapping of neutron field represents an essential and crucial part of planning BNCT treatment (especially for patients suffering from brain tumor Glioblastoma Multiforme).